Pengaruh Gaya Kepemimpinan Transformasional Kepala Sekolah terhadap Efektivitas Administrasi Pendidikan - Tanjung, Rezfani Ummi Humairah; Hanafiah, Muhammad Ali; Tamrin, Muhammad (Prodi PIAUD STAI Sumatera Medan, 2025)
This study aims to describe the implementation of transformational leadership by the principal and to analyze teachers’ and staff perceptions regarding its impact on educational administration effectiveness at SMK Bina Taruna 1 Medan. This research employed a qualitative approach with a case study design using in-depth interviews, observation, and document analysis involving eleven informants consisting of the principal, vice principals, teachers, and administrative staff. Data analysis was carried out using Miles, Huberman, and Saldana’s model, including data condensation, data display, conclusion drawing, and verification through source and method triangulation. The findings indicate that the principal has applied transformational leadership through moral exemplification, visionary motivation, encouragement of innovation, and individualized consideration. Teachers and staff expressed generally positive perceptions, shown through increased engagement, open communication, and the development of a more collaborative work culture. However, obstacles still exist in terms of policy consistency, digital-based administrative human resource readiness, and optimization of standard operational procedures. This study presents novelty by integrating transformational leadership and administrative effectiveness within a vocational school context in Medan through an in-depth qualitative approach. The results are expected to serve as a reference for developing transformative leadership models and enhancing sustainable school administrative governance.